Prevalence of diabetes among hypothyroid subjects - Ashrafuzzaman, SM; Taib, AN; Rahman, R; Latif, ZA (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):129-132 The abstract of this article is available on the PubMed website